TIBBIYOT YO‘NALISHIDA TAHSIL OLAYOTGAN O‘QUVCHI-QIZLARNI KASBIY FAOLIYATGA JISMONIY TAYYORGARLIK DARAJASINI SAMARALI OSHIRISH METODOLOGIYASI - Norkulov, D.R. (SCIENCE and SOCIETY, 2022)
The article explores the process of short-term training of students studying in vocational schools, taking into account the proposed methodology for effective improvement of physical fitness for professional activities in the conditions of high ambient temperature.